Numerical Simulation of Fatigue Damage and Shape Instability Behavior of Steel 40Cr by the Damage-Coupled Crystal Plastic Model - Wu, G.C.; Li Y., F.; Pan, X.D.; Wang, G.L. (Проблемы прочности, 2017)
A representative volume element is developed based on the Voronoi tessellation to reveal the mechanism of shape instability behavior. In the model, a damage-coupled crystal plastic model is established to describe the shape instability behavior. The heterogeneity of materials is introduced into the model with the aim of simulating the microstructure of materials. The experimental and simulation results show that the fatigue damage in the elastic deformation stage with high cyclic stress level is the initial motivation of shape instability behavior. The cyclic softening and ratcheting properties of materials accelerate the plastic strain accumulated rate.